Selected intermediate to early-advanced works for piano solo by Violet Balestreri Archer: An analysis for teaching and performance - Soo, Rosalyn Wai-yan (Université d'Oklahoma, 1997)
The ensuing four chapters present analyses of the selected works. The discussion of each composition begins with a brief introduction about its background, stylistic traits, and influences. A structural analysis follows, addressing traditional musical parameters and how they are manipulated by Archer's contemporary style. Analytical elements include the investigation of main sections, tonal areas, character, compositional devices, and style. An additional aesthetic goal of the analysis is to consider the musical elements of the works with regard to a listener's possible perceptions.